2017
DOI: 10.1371/journal.pone.0186852
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the proliferation marker Ki-67 in a large prostatectomy cohort

Abstract: The tumor proliferation index marker Ki-67 is strongly associated with tumor cell proliferation, growth and progression, and is widely used in routine clinicopathological investigation. Prostate cancer is a complex multifaceted and biologically heterogeneous disease, and overtreatment of localized, low volume indolent tumors, is evident. Here, we aimed to assess Ki-67 expression and related outcomes of 535 patients treated with radical prostatectomy. The percentage of tumor epithelial cells expressing Ki-67 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 35 publications
0
40
0
1
Order By: Relevance
“…The nuclear antigen recognised by the Ki67 antibody is expressed in proliferating cells but absent in resting cells . Since its discovery in 1983 by Gerdes et al , Ki67 assessed by immunostaining has been studied extensively as a prognostic and predictive marker, predominantly in hormone receptor‐positive breast cancer, but also in other tumours . For example, presurgical Ki67 has been shown to be a marker for recurrence‐free survival and, in the neoadjuvant setting, a marker for endocrine‐resistant tumour that may require more aggressive treatment .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nuclear antigen recognised by the Ki67 antibody is expressed in proliferating cells but absent in resting cells . Since its discovery in 1983 by Gerdes et al , Ki67 assessed by immunostaining has been studied extensively as a prognostic and predictive marker, predominantly in hormone receptor‐positive breast cancer, but also in other tumours . For example, presurgical Ki67 has been shown to be a marker for recurrence‐free survival and, in the neoadjuvant setting, a marker for endocrine‐resistant tumour that may require more aggressive treatment .…”
Section: Introductionmentioning
confidence: 99%
“…1 Since its discovery in 1983 by Gerdes et al, 1 Ki67 assessed by immunostaining has been studied extensively as a prognostic [2][3][4][5][6][7][8][9][10][11] and predictive 4,6,9,12,13 marker, predominantly in hormone receptor-positive breast cancer, but also in other tumours. [14][15][16][17][18] For example, presurgical Ki67 has been shown to be a marker for recurrence-free survival 19 and, in the neoadjuvant setting, a marker for endocrine-resistant tumour that may require more aggressive treatment. 20 Excellent intra-observer reproducibility under controlled pre-analytical and staining conditions 21 has contributed to the body of evidence showing the potential of Ki67 immunohistochemistry assay to be implemented in hospital laboratories as a cost-effective part of clinical management.…”
Section: Introductionmentioning
confidence: 99%
“…Cell proliferation was previously reported to be positively correlated with high Gleason score in patients. 20 The downregulation of ELL2 in high Gleason score prostate tumor specimens and increased proliferation in prostate cancer cells treated with ELL2 knockdown suggests that ELL2 can modulate proliferation of prostate epithelial cells.…”
Section: Discussionmentioning
confidence: 96%
“…Our Ki67 scores in the validation cohort were reviewed by a single observer and therefore interobserver differences in scoring of Ki67 could not be assessed in our study. Other PCa studies, consistent with Ki67 data from other cancer types, have demonstrated that the interobserver variability for Ki67 scoring is low provided that a sufficient sample is systematically assessed . Ideally, a consensus in AZGP1 and Ki67 staining techniques and interpretation in PCa, similar to that recently achieved in breast cancer, would aid AZGP1 and Ki67 IHC in becoming more firmly established in routine clinical practice.…”
Section: Discussionmentioning
confidence: 68%
“…Other PCa studies, consistent with Ki67 data from other cancer types, have demonstrated that the interobserver variability for Ki67 scoring is low provided that a sufficient sample is systematically assessed. 51 Ideally, a consensus in AZGP1 and Ki67 staining techniques and interpretation in PCa, similar to that recently achieved in breast cancer, 52 would aid AZGP1 and Ki67 IHC in becoming more firmly established in routine clinical practice. In the validation of our biomarkers, we also used TMA cores rather than whole slide sections to determine IHC activity, which does not reflect clinical practice.…”
Section: Discussionmentioning
confidence: 92%